Thai women’s experiences of and responses to domestic violence - Chuemchit M; Chernkwanma S; Somrongthong R; Spitzer DL (Dove Medical Press, 2018)
Montakarn Chuemchit,1 Suttharuethai Chernkwanma,1 Ratana Somrongthong,1 Denise L Spitzer2 1College of Public Health Sciences, Chulalongkorn University, Patumwan, Bangkok, Thailand; 2Institute of Feminist and Gender Studies, University of Ottawa, Ottawa, ON, Canada Purpose: Domestic violence has been linked to many health consequences. It can impact women’s mental, physical, sexual, and reproductive health, and all of these effects can be long lasting. Despite the growing awareness of the deleterious effects of domestic violence in Thailand, there have been few nation-wide studies that have examined the issue and its consequences. In fact, Thailand has not examined intimate partner violence incidence for the past 20 years. This study aimed to investigate the consequences of domestic violence across the country. Subjects and methods: A cross-sectional study was conducted in four areas of Thailand: central, southern, northern, and northeastern. One province in each area was selected by simple random sampling techniques. One thousand four hundred and forty-four married or cohabiting females in a heterosexual union, aged 20–59 years, were included in the sample and were interviewed about their experiences of psychological, physical, and sexual violence by their male partners. Results: One thousand four hundred and forty-four women completed the interviews. Sixteen percent of respondents encountered domestic violence in its various psychological, physical, or sexual forms. In the majority of cases, all forms of domestic violence were exerted repeatedly. Four-fifths of women who faced domestic violence reported that it had an impact on their physical and mental health as well as employment. This study also found that half of the domestic violence survivors reported their children had witnessed violent situations. These women exercised four coping strategies to deal with their domestic violence: 1) counseling; 2) requesting help from others; 3) fighting back; and 4) running away from home. Conclusion: The findings confirm that domestic violence has implications that extend beyond health and result in the deterioration of the quality of women’s lives. These results underscore that domestic violence is a serious problem that must be addressed in Thai society. Keywords: domestic violence, intimate partner violence, Thailand, prevalence, consequences, violence countrywide, health impact, coping strategy